Impacts of long-term weed management on the diversity and abundance of grasses in banana plantation slopes in Davao City, Philippines - Rasco, Eufemio T. Jr.; Oguis, Georgianna Kae R.; Ragas, Richie Eve G.; Masacupan, Kristian T.; Camarillo, Ed Levi C.; Santos, Stephen Matthew B. (2012)
Banana is one of the main export products in the Philippines. The growing demand for banana products generates a need for plantation expansion even in erosion-prone areas like slopes. Effective farming practices in slopes are therefore needed to conserve the soil and establish a sustainable production. One of these systems is weed management, which is a critical component of farming practice in sloping lands. A 3-year study was conducted compare manual and chemical (paraquat and glyphosate) weed management on the abundance and diversity of grasses in a banana plantation. Counts, biomasses, seed bank, and diversity indices of grasses were compared in identical experiments in 15% and 25% slopes. From the seed banks, 7 grass species were observed: Cyperus brevifolius, Cynodon dactylon, Eleusine indica, Imperata cylindrica, Paspalum conjugatum, Digitaria ciliaris, and Digitaria longiflora. Generally, there was a decreasing trend in the seed bank accounts in both manual and chemical plots of 15% and 25% slope. However, the difference between treatments were not significant. Chemical treatment reduced the general counts and biomass of monocot weeds, but this effect was generally not significant. Chemical treatments significantly reduced the counts of P. conjugatum in 15% slope and the biomass of E. indica in 25% slope in the field. C. dactylon was found to be the dominant species in the field because of its early establishment in the slopes, its spreading growth and its allelopathic properties, which suppressed other species. There was a significant increase in diversity in both treatments on two slopes, but chemical plots had a significantly higher diversity compared to manual plots. Chemical weeding was also less expensive and less laborious than manual weeding.
Keywords: Banana plantations--Davao City--Philippines; Weed management